The syndemic and one health nature of pandemics: Arguments for renewed attention to intelligence management - Magalhães, J.; Correia, T.; Inês Fronteira; Sidat, M.; Barros, F.; Daniel-Ribeiro, C.; Delgado, A.; Ferrinho, P. (Handbook of research on essential information approaches to aiding global health in the one health context, 2021)
The interdependence of humans, animals, plants, and their social and abiotic environment is highlighted by past and recent pandemics. A good example to understand and tackle threats to ecosystems is the COVID-19 pandemic. A syndemic is a complex and multilevel phenomenon of epidemics interacting synergistically at individual, societal, and environmental levels. Understanding the syndemic nature of pandemics will facilitate the adoption of a One Health approach to improve planetary health. To address the eco-complexity underlying One Health issues, the development of intelligence management systems through a planetary perspective is of key importance. This requires the capacity to capture, process, and communicate data on human, animal, and plant health and well-being, and on their social and environmental determinants. The implementation of such systems will need political commitment at all levels of action, deployment of adequate resources and expertise, reliable and comprehensive data flowing pathways through interoperable, flexible, and secure data sharing systems.